2020
DOI: 10.1161/strokeaha.120.030397
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Large Vessel Occlusion Stroke During New York City’s COVID-19 Outbreak

Abstract: Background and Purpose: The 2019 novel coronavirus outbreak and its associated disease (coronavirus disease 2019 [COVID-19]) have created a worldwide pandemic. Early data suggest higher rate of ischemic stroke in severe COVID-19 infection. We evaluated whether a relationship exists between emergent large vessel occlusion (ELVO) and the ongoing COVID-19 outbreak. Methods: This is a retrospective, observational case series. Data were collected from all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
98
1
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 16 publications
8
98
1
7
Order By: Relevance
“…1 2 5 29 38 Among COVID-19-positive patients in New York presenting with emergent LVO, more than 90% had elevated D-dimer levels and 42% presented with symptoms of acute ischemic stroke rather than typical respiratory symptoms. 29 In addition, patients presented with stroke days before demonstrating symptoms of COVID-19, suggesting that there may be an increased risk of thrombosis even in the early phase of the disease. 5 39 A recent review found a consistent increase in D-dimer levels among patients with severe compared with non-severe COVID-19 disease.…”
Section: Mechanisms Of Stroke In Covid-19mentioning
confidence: 99%
“…1 2 5 29 38 Among COVID-19-positive patients in New York presenting with emergent LVO, more than 90% had elevated D-dimer levels and 42% presented with symptoms of acute ischemic stroke rather than typical respiratory symptoms. 29 In addition, patients presented with stroke days before demonstrating symptoms of COVID-19, suggesting that there may be an increased risk of thrombosis even in the early phase of the disease. 5 39 A recent review found a consistent increase in D-dimer levels among patients with severe compared with non-severe COVID-19 disease.…”
Section: Mechanisms Of Stroke In Covid-19mentioning
confidence: 99%
“…Even the data presented in table 1 showed that the numbers of LVOs quadrupled at their hospital. 25 , 48 In fact, the reduction in telestroke consults and total stroke admission started before releasing the 2 publications. 2 , 23 Patients were delaying presentation to the hospitals due to fear of the contagion.…”
mentioning
confidence: 99%
“…In fact, the Fire Department of the City of New York reported an almost 4-times normal rate of patients being dead on emergency medical service arrival during the pandemic period. 48 The authors appear to be confusing the quarantine effect on stroke broadly (which has also been well documented) in the literature with the actual scientific pathophysiology of the disease. 49 , 50 COVID-19 is been overwhelmingly demonstrated to be pro-thrombotic and causes clots to form in a wide range of organ systems… whether fractures in systems of care, changed referral patterns, ED resource re-allocation, social distancing, or self-isolation result in decreased stroke presentation to hospitals, the pro-thrombotic reality of COVID-19 is scientifically unarguable.…”
mentioning
confidence: 99%
See 2 more Smart Citations